Experimental and numerical investigation of multi-layered honeycomb sandwich composites for impact mechanics applications - Al Ali, A.; Arhore, Edore G.; Ghasemnejad, Hessam; Yasaee, Mehdi (Elsevier, 2024)
This project aims to investigate the design of a multi-layered sandwich composite and its performance under impact loading conditions. An experimental and numerical assessment was performed to conclude the effect of increasing the layers of sandwich panels. Three specimens of four different sandwich panel configurations were manufactured to be tested. The skin of the sandwich panels comprises a twill carbon-reinforced epoxy resin, whereas the core consists of a 2D Nomex honeycomb core. The panels are then subjected to transverse impact loading to investigate their impact behaviour. These experimental results are then used to verify numerical models constructed in LS-Dyna. The models of the honeycomb-reinforced sandwich panels are investigated using MAT-054 and MAT-142 material cards in LS-Dyna to find the most economical computational approach. Finally, the energy absorption characteristics calculated during the experimental and numerical work are used to conclude the multi-layered sandwich composite's performance and provide design recommendations. The findings suggest that by increasing the core and shell numbers through the thickness of the panel, the specific energy absorption capability will increase.
Keywords: Multi-layered; Sandwich; Impact; LS-Dyna